Beautiful Deaths and Heard Gazes - Staton, David (Eikón / Imago, 2021)
Viewers frequently encounter “normative” prescriptions and perceptions through photographs of how images depicting death and dying should loo and, cognitively, how those images ought to be received. In such encounters, varying fundamental views or cultural myths surrounding death and dying, how it is envisioned, how it is, literally, pictured dictate a particular way of seeing and being. This article considers visual representations made of individuals who choose to enact Death With Dignity provisions to end their lives on their own terms and on their own time line. By an interrogation of a corpus of DWD images, the author investigates how such representations challenge a particular cultural logic. This reconsideration may lead to an awareness; a reasoning, creating a space in which reality is constructed beneath the viewer’s gaze. Such a reality, relies on an embodied or pragmatic aesthetic and is co-constituted by expressions of power that emanate from image and viewer. The author dubs this modality the heard gaze; a vision in which the past, present, and future are fused and subject becomes object or vessel of understanding by perceiving a visual, auditory “cue”.